Potensi ekstrak maggot lalat tentara hitam Hermetia illucens (Linnaeus) dalam regulasi mekanisme antioksidan selular dan antiradang: Kajian in silico: The potential of black soldier fly Hermetia illucens (Linnaeus) maggot extracts in the regulation of cellular antioxidant and anti-inflammatory mechanisms: In silico study - Sulistiyani; Firdaus, Muhamad Fajar; Sigiro, Ria Heni; Nawangsih, Abdjad Asih; Purwanto, Ukhradiya Magharaniq Safira; Andrianto, Dimas (Jurnal Entomologi Indonesia, 2023)
The potential of black soldier fly (Hermetia illucens (Linnaeus), BSF) maggots as the source of biopharmaca, has not been extensively studied. This research aimed to identify bioactive compunds in BSF maggot extract that potentially activate antioxidant signaling mechanism. BSF maggots fed with vegetable waste were extracted based on maceration method with water, methanol, and acetone as solvents. Forty bioactive compounds were identified by liquid chromatography-mass spectrometry: 15 were in the aqueous extract, 13 were from methanolic extract, and 12 were in the acetone extract. Most of those compounds (90%) were having high bioavailability score (= 0.55 or more) and relatively low toxicity (500 mg/Kg<LD50<5000mg/Kg BW). Molecular docking predicted that there were 26 bioactive compounds potential to activate cellular antioxidant signaling through activation of NRF2 transcription factor, better than the commercial NRF2 activator. The aqueous extract compound with PubChem CID: 73775828 was the best one that inhibited NRF2 signaling by binding to Keap-1 protein (PDB ID: 6FFM) with Gibbs free energy (Î”G) = -6.08 Kcal/mol and dissociation constant (Kd) = 3.58 í— 10-5 µM. Whereas inhibition of inflammation via NF-kappa B signaling was shown by an aqueous extract compound verpacamide A which bound inhibitor NF-kappa B kinase (IKK2) (PDB ID: 4KIK) with Î”G = -5.024 kcal/mol; Kd = 0.207 í— 103 µM. This potency was better than that of aspirin. In conclusion, BSF maggot extracts are source of biopharmaca with potential cellular antioxidant and anti-inflammatory activity.